Exposure of Covid-19 Vaccination Information and Willingness to Receive Vaccination - Firda Yanuar Pradani; M. Ezza Azmi Fuadiyah; Mutiara Widawati (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2021)
One of the strategies to curb the Covid-19 spread was administering the Covid-19 vaccine as it remains the most effective means to achieve control of the pandemic. As mandated by Minister of Health Decree Number 10/2021, Pangandaran District has to conduct Covid-19 vaccination to 341.216 individuals as the target population. Per July 26th, the Covid-19 vaccination coverage is still below 10% of target with Parigi, Sidamulih, and Mangunjaya Subdistricts as subdistricts with the lowest vaccination coverage. Vaccine hesitancy and misinformation present major barriers to achieving community coverage and immunity. This was a cross-sectional rapid survey conducted in August 2021, held in subdistrict Parigi, Sidamulih, and Mangunjaya of Pangandaran District, West Java Province. There was a total of 915 samples participated through an electronic questionnaire. Data were analyzed as univariate, and chi-square was used in bivariate analysis. There’s a significant relationship between the exposure of information about the Covid-19 vaccine with willingness to receive the vaccination